Early Modern Wales, c. 1525–1640 - Jones, J. Gwynfor. author. aut Link
XV, 288 p.
Keywords: This work is intended to examine the main trends in Wales during the century following the Tudor settlement of Wales. Emphasis is placed on the social structure, the framework of government and administration, and the Reformation Settlement. The Stuart accession and its repercussions are also considered in relation to political, economic and cultural affairs, as well as the attitudes of the Welsh gentry to a new environment on the eve of the Civil War. The work makes ample use of contemporary sources to examine each aspect of the political, governmental and religious life of Wales.